IMMUNOGENESITY OF SPESIFIC PROTEIN MOLECULAR WEIGHT 16 KDa (PS16) LEAF OF SIAM CITRUS INFECTED BY CITRUS VEIN PHLOEM DEGENERATION (CVPD) DISEASE - Made Sritamin; Aulanni ‘am Aulanni ‘am; IGP. Wirawan; Liliek Sulistyowati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Citrus Vein Phloem degeneration (CVPD) is an important citrus disese, which damaged citrus plantation and causing decrease of citrus production. In Indonesia, the CVPD disease caused by Liberobacter asiaticum bactery and the disease spread out by vectir insect Diaphorina citri and using infected bud in wood grafting. In infected citrus plant, two specific protein molecules with molecular weigt 16 kDa and 66 kDa are found. These protein molecules are not found in healthy citrus plant. The immunogenicity of PS16 accumulated on leaf of citrus plant infected by CVPD is known yet. The research material were leaves of citrus plant infected CVPD, leaves of healthy citrus plant and reagent used these research are for isolation of the total protein leaf of citrus plant, SDS-PAGE electroforesis, electroelution of PS16, ELISA Methods, Dot-Blot Method, anti-PS16 as aprimery antibody and secondary antibody is anti-Rabbit IgG Conjugated AP. The result of the research showed that of PS16 accumulated on leaf of citrus plant infected CVPD has immunogenic character. It is indicated by increase of the titer anti-PS16 after first immunization ang 2nd booster by indirect ELISA method and can be used to induce antibody (anti-PS16) and so showed that positive reaction between PS16 with anti-PS16. It is indicated by purples dark blue on cellulose membrane by Dot Blot method.